2019
DOI: 10.29138/ijebd.v2i2.854
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leadership, Adversity Quotient on Organizational Commitment of PT. Jaya Konstruksi Manggala Pratama Tbk

Abstract: Purpose: The purpose of this study was to describe and analyze the influence of corporate leadership, adversity quotient on organizational commitment. Design/methodology/approach: This research used a quantitative approach with survey method. The sample of this research is the whole 204 staff in PT. Jaya Konstruksi Manggala Pratama Tbk is done randomly. Findings: 1) there is a direct positive influence leadership on organizational commitment; (2) there is a direct positive influence adversity quoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
1
3
0
2
Order By: Relevance
“…The influence dimension 𝑝 41 was .0396 or 3.96 %, indicating that the effect of adversity quotient on teachers' commitment is shallow. The finding corresponds with the evidence presented by Subagyo et al (2019) that OC was directly affected positively by the AQ.…”
Section: Findings and Discussionsupporting
confidence: 91%
“…The influence dimension 𝑝 41 was .0396 or 3.96 %, indicating that the effect of adversity quotient on teachers' commitment is shallow. The finding corresponds with the evidence presented by Subagyo et al (2019) that OC was directly affected positively by the AQ.…”
Section: Findings and Discussionsupporting
confidence: 91%
“…Penelitian ini mengasumsikan bahwa adversity quotient dan occupational stress berpengaruh terhadap komitmen organisasi. Subagyo et al (2019) 2017) Adversity Quotient adalah kemampuan seseorang untuk mengatasi dan menghadapi kesulitan, sekaligus bagaimana ia dapat bertahan di tengah kesulitan. Singh dan Sharma (2017) dalam penelitian yang mereka lakukan menjelaskan bahwa orang-orang yang memiliki Adversity Quotient yang tinggi dapat terus bergerak maju dengan sukses dan terus meningkat dalam kehidupan mereka karena mereka memiliki kemampuan untuk menanggung kesulitan yang cukup besar.…”
Section: Kerangka Penelitianunclassified
“…Studi yang dilakukan Chin dan Hung, 2008) dan Harriman (2016) juga menjelaskan bahwa adversity quotient merupakan salah satu faktor yang mempengaruhi seorang karyawan untuk tidak meninggalkan perusahaan tempat mereka bekerja. Hasil penelitian Subagyo et al (2019) menjelaskan bahwa adversity quotient berpengaruh positif dan signifikan terhadap komitmen organisasi. Berdasarkan pendapat dan pernyataan dari peneliti terdahulu, maka peneliti menarik hipotesis sebagai berikut : H1.…”
Section: Kerangka Penelitianunclassified
“…The high AQ teachers, such as control, origin ownership, reach, and endurance [17], tend to involve the teachers' emotional attachment to, identification with, and involvement in the school organization [35]. The scholar's studies [45], [46] also proved that AQ influences organizational commitment. Based on the previous studies, the fourth hypothesis in this study is: AQ has a direct effect on organizational commitment (H4).…”
Section: Introductionmentioning
confidence: 99%
“…The indicators of AQ, such as control, origin ownership, reach, and endurance [17] if sufficient conditions and consistent for a long time can stimulate organizational commitment manifested in affective, continuance, and normative commitment [35] and then implicate enhancing teachers' OCB manifested in altruism, conscientiousness, sportsmanship, courtesy, and civic virtue [9]. The research result conducted by researchers [45], [46] also claimed that AQ related to organizational commitment, while the several studies [36]- [44] indicated that organizational commitment influences teachers' OCB. Based on the previous argument and studies, the sixth hypothesis in this study is: AQ has an indirect effect on teachers' OCB mediated by organizational commitment (H6).…”
Section: Introductionmentioning
confidence: 99%